LABORATORY EVALUATION OF ASPHALT CONCRETE MIX MADE WITH HIGH BONDING ASPHALT HBA-80 - Kadarusman, Utang
LABORATORY EVALUATION OF ASPHALT CONCRETE MIX MADE WITH HIGH BONDING ASPHALT HBA-80, Utang Kadarusman, 1999, Program Magister Sistem dan Teknik Jalan Raya, Program Pascasarjana, Institut Teknologi Bandung. Flexible pavements made with conventional bitumen do not have the properties to cope satisfactorily with traffic loading that is increasing in magnitude and frequency, particularly in adverse climatic conditions. Research has focused on modifying the properties of conventional bitumen by additives that enhance binder durability and temperature susceptibility while retaining flexibility and resistance to permanent deformation. This thesis describes a laboratory evaluation of a polymer-modified bitumen called HBA-80. The properties of HBA-80 are compared with those of conventional AC-60 as are the properties of asphalt concrete surfacing mixes made with these binders. Penetration tests made before and after the Rolling Thin Film Oven Test (RTFOT) indicate that in the higher temperature range (30Â°C - 35Â°C) HBA-80 is less temperature susceptible than AC-60. Rotational viscometer tests before RTFOT show that the viscosity of HBA-80 is considerably higher than that of AC-60 but more temperature susceptible. Durability was assessed in terms of RTFOT, retained Penetration after RTFOT, and change in Softening Point was not shown equally of result. Optimum bitumen content for the mixes made with HBA-80 and AC-60 binders were determined by Marshall analysis to be the same i.e. 6.30%. The corresponding values of Index of Retained Stability were determined to be 89.90% and 83.58%. At optimum bitumen content there is the same trend in indirect tensile strength and indirect tensile resilient modulus determined for both mixes over a range of temperatures. In the higher temperature range the mix made with HBA-80 exhibits marginally higher values for these parameters and in the lower temperature range is less temperature susceptible. In the Wheel Tracking Test the mix made with HBA-80 is better able to resist deformation at higher temperatures but has almost identical performance with the AC-60 mix at lower temperatures